IMPLEMENTASI KEBIJAKAN PROGRAM TPS3R DALAM PENANGANAN SAMPAH DI DESA ADAT TANJUNG BENOA BERDASARKAN ATAS PERATURAN BUPATI BADUNG NO.48 TAHUN 2018 - Putri, Ni Made Rianti Nitiyasa; Wirantari, I Dewa Ayu Putri; Wijaya, Komang Adi Sastra (CITIZEN CHARTER; Vol 3 No 2 (2023): Administrasi Publik 2023, 2024)
The TPS3R program is an innovation program in the field of waste management and waste handling. The TPS3R program aims to reduce the quantity of waste production and/ improve the characteristics of the waste to be processed, as well as to ensure that the accumulation of waste in landfills is reduced. Researchers limited this research to the Tanjung Benoa Traditional Village. In practice, there are still problems related to the quantity and quality of the facilities and infrastructure used, there are no strict sanctions governing people who violate the regulations, and the targets of the TPS3R program in Tanjung Benoa Traditional Village have not been achieved. The purpose of this research is to find out how the TPS3R Program is implemented in dealing with waste problems in the Tanjung Benoa Traditional Village. This study uses descriptive qualitative methods with data collection techniques in the form of observation, interviews, and documentation. The results of related research were analyzed using three aspects according to Charles O. Jones, namely organization, interpretation, and application or application which showed that the TPS3R program in the Tanjung Benoa Traditional Village was not optimal because there were still problems in several aspects such as limited financial resources used for expenses. operationally, the facilities and infrastructure that are used as supporting factors have not been able to support the program optimally, there are still people who are reluctant to comply with regulations that hinder the program implementation process, and there are no strict sanctions that can create a deterrent to people who violate them.